An integrated model of the structural evolution of the central Brooks Range foothiUs, Alaska, using structural geometry, fracture distribution, geochronology, and microthermometry - Duncan, Alec; Hanks, C.; Wallace, W.; O'Sullivan, P.; Parris, T. (AMER ASSOC PETROLEUM GEOLOGIST, 2012)
Episodic deformation, triangle zone development, and related back thrusting in the central Brooks Range foothills are major factors in the distribution of fractures and the thermal history of rocks involved in the deformation. Structural reconstructions suggest that the rocks forming the Endicott Mountains allochthon, the youngest and northernmost part of the orogen during its first phase, were emplaced during the Early Cretaceous (Valanginian) at temperatures approximately 150°C. Fractures associated with that deformation are filled with synkinematic calcite cement, indicating that they formed in the presence of fluids. After a period of quiescence during the Late Cretaceous, renewed deformation involved the shortening of the existing orogenic wedge and the development of a triangle zone and overlying back thrust in adjacent mid- to Late Cretaceous rocks of the foreland basin. This later de-formational event and subsequent uplift resulted in two sets of uncemented barren fractures that formed in all parts of the fold and thrust belt. Restriction of cement-filled fractures to the older and structurally deeper parts of the orogen implies that the youngest and most obvious fractures visible at the surface developed at shallow depths and temperatures and thus may not have been an important factor in petroleum migration. © 2012. The American Association of Petroleum Geologists. All rights reserved.